P209 What makes expedited partner therapy (EPT) and accelerated partner therapy (APT) work for partner notification for bacterial stis? a systematic review of interventions. (8th June 2017) - Mapp, Fiona; Pothoulaki, Maria; Vojt, Gabriele; Estcourt, Claudia; Wayal, Sonali; Cassell, Jackie; Kanwar, Tavishi; Patel, Krish; Flowers, Paul; Copas, Andrew; Johnson, Anne; Low, Nicola; et al.
Abstract : Introduction: Expedited Partner Therapy (EPT) treats the sex partners of persons with STIs without prior clinical evaluation. These interventions have been shown to reduce rates of re-infection and treat a higher proportion of sex partners. EPT which includes remote medical assessment of sexual partners is known as Accelerated Partner Therapy (APT) and meets UK prescribing guidance. Understanding the sequential active behaviour change components of such partner notification (PN) interventions and their use of theory, enables their optimisation and translation to the UK health context. Methods: We searched eight databases for studies detailing EPT and APT interventions for STIs implemented in high-income countries which included process and outcome data. Abstracts were screened and full-text articles analysed. Data were extracted relating to population, context, intervention components and associated behaviour change techniques (BCTs). Results: We included 15 of 723 studies covering interventions implemented between 1996–2013 in the UK and USA. EPT interventions are composed of complex sequences of diverse components, representing heterogeneous 'relay' behaviour change interventions. They involve diverse behavioural targets and target populations (index patient, partners, healthcare professionals). However they employ a broadly consistent range of behaviour change techniques including: 'how to perform a behaviour' and 'information about health consequences.' Discussion: EPT interventions are atheoretical, developed in response to patient and provider needs. Systematically identifying the key behaviour components and processes involved in EPT/APT may help explain intervention effectiveness. Developing an explicit theoretical framework using identified BCTs will help in training healthcare professionals to deliver EPT/APT, improving generalisability of interventions and PN outcomes.